THE GOTHIC AS AN ARTISTIC AND STYLISTIC FEATURE IN SHORT PROSE BY IVAN FRANKO - Гросевич, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyses the short prose by Ivan Franko in the paradigm of gothic poetics, determines and systematizes the complex of elements of gothic paradigm in the writ’s texts, substantiates the philosophical doctrine of theodicy as one of the fundamental platforms of the whole literary gothic in general and analizes Ivan Franko’s writings in particular.